Modification of Indonesian Kaolinite-Based Silica Coarse (SC) for RNA Extraction Method of SARS-CoV-2 - Marintan, Marchia Marthalena; Sjatha, Fithriyah; Nurani, Dita Arifa; Krisnandi, Yuni Krisyuningsih; Sariman, Sariman (Science and Technology Indonesia, 2024)
One of the strategies to overcome the COVID-19 disease is through rapid diagnostic tests using the Reverse-Transcriptase Polymerase Chain Reaction (RT-PCR) test. The RT-PCR test is a detection and quantification test of nucleic acids, initiated by the pre-analytical step of purification of the nucleic acids. Purification of nucleic acid requires silica-based materials as a solid phase-extraction matrix or column. Herein, Silica Coarse (SC) in the form of suspension and powder columns; was prepared from natural Indonesian Kaolinite as an alternative extraction column to binding RNA of SARS-CoV-2. The RNA binding and releasing ability in SC was enhanced with the support of chaotropic agents in the form of Na+ and Guanidium+ as charged balancing cations, embedded in the silicate layer inside the kaolinite framework. SC, which has been supported with Na+ and Guanidium+ respectively, then studied its physicochemical characteristics using FTIR spectroscopy, X-ray diffraction technique, scanning electron microscopy, and BET surface area and pore size measurement. This work shows that the modified SC suspension column could extract RNA of SARS-CoV-2 that amplified better in the RT PCR test than SC powder columns, with the initial Ct value of all the SARS-CoV-2 specimens in the range < 20.